The Use of Parody Content as a Marketing Tool for @danielalvinjr Among Gen Z - Haikal Fajrin; Siti Khumayah; Aghnia Dian Lestari (Greenation Publisher & Yayasan Global Resarch National, 2026)
The rise of social media, particularly TikTok, has spurred the emergence of various types of creative content used as marketing strategies, including parodies. Gen Z, who prefer content that is simple, entertaining, and relatable to everyday life, are the most prominent participants in this phenomenon. The TikTok account @danielalvinjr consistently uses parody content to build his personal brand and reach Gen Z, particularly in the city of Cirebon. The objective of this study is to understand how Gen Z perceives the personal branding of TikTok influencers, identify the personal branding strategies employed by @danielalvinjr, and examine the variations in Gen Z’s perceptions of the parody content presented. In this study, a descriptive qualitative approach was used, and data collection was conducted through in-depth interviews with the creator as the primary informant and Gen Z in the city of Cirebon as supporting informants. The research indicates that parody content is viewed as an authentic means of personal branding. Gen Z evaluates personal branding strategies that emphasize consistency, uniqueness, and the delivery of messages without direct solicitation positively. Differences in Gen Z’s perceptions indicate that parody content serves not only as entertainment but also as a relevant social reflection of the dynamics of Gen Z’s lives.